3′UTR SL-IV and DB1 Regions Contribute to Japanese Encephalitis Virus Replication and Pathogenicity - Xing, Jinchao; Zhang, Youyue; Lin, Ziying; Liu, Lele; Xu, Qiang; Liang, Jiaqi; Yuan, Zhaoxia; Huang, Cuiqin; Liao, Ming; Qi, Wenbao (Frontiers in Veterinary Science, 2021)
Japanese encephalitis virus (JEV), a mosquito-borne flavivirus that causes fatal neurological disease in humans, is one of the most important emerging pathogens of public health significance. JEV is maintained in an enzootic cycle and causes reproductive failure in pigs. Notably, the shift in JEV genotypes is not fully protected by existing vaccines, so the development of a candidate vaccine is urgently needed. In this study, we compared pathogenicity between Japanese encephalitis virus SA14 and BJB (isolated from humans in the 1970s) strains. We found that the BJB strain was attenuated in mice and that there was no case fatality rate. The growth rate of BJB was higher than SA14 virus in BHK-21 cells. Based on the sequence alignment of the viral genome between the SA14 and BJB virus strains, some mutations at sites 248, 254, 258, and 307 were observed in the 3′ untranslated region (3′UTR). The 3′UTR of JEV plays a very important role in the viral life cycle. Furthermore, using a reverse genetic system, we conducted and rescued the parental JEV strain SA14 (T248, A254, and A258) and the mutant virus rSA14-3′UTRmut (T248C, A254G, A258G, and 307G). Through an analysis of the RNA secondary structure model of the 3′UTR, we discovered that the mutations of T248C, A254G, and A258G reduced the apiculus ring and increased the lateral ring significantly in the stem-loop structures IV (SL-IV) structure region of 3′UTR. Moreover, the insertion of 307G added a ring to the dumbbell structure 1 (DB1) structure region. Strikingly, these RNA secondary structure changes in 3′UTR of rSA14-3′UTRmut increased viral negative chain RNA production and enhanced the replication ability of the virus in BHK-21 cells. However, in vivo mouse experiments illustrated that the rSA14-3′UTRmut virus significantly decreased the neurovirulence of JEV. These results affirmed that the JEV SL-IV and DB1 regions play an important role in viral proliferation and pathogenicity. Taken together, we complement the study of RNA element function in the 3′UTR region of JEV by providing a new target for the rational design of live attenuated candidate vaccines and the increase of virus production.